Memahami Kompleksitas Hukum: Penanganan Penyalahgunaan Narkotika oleh Anak di Kawasan Makassar - Murdiono Murdiono; Ayu Chairun Nisa (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This research aims to analyze the application of the law towards criminal abuse of narcotics committed by children in Makassar City (Case Study Decision: Number 8/Pid.Sus-Anak/2020/Pn Mks). The research method used is a non-doctoral (empirical) legal research method. This research uses primary and secondary data in studying analyzing, and analyzing norms, rules and judge considerations in court decisions regarding the abuse of narcotics crimes committed. by children in Makassar City.